Multiple learning contexts and the development of life skills among Canadian junior national team biathletes - Jørgensen, H.; Lemyre, P.-N.; Holt, N. (Journal of Applied Sport Psychology, 2020)
The purposes of this study were to identify and explore (a) the life skills learning contexts experienced by Canadian junior national team biathletes and (b) the ways in which they learned life skills in these contexts. Nine members of the Canadian junior national biathlon team participated in individual semi-structured interviews. Results of thematic analysis revealed 3 life skills learning contexts: sport, school/work, and family. Participants reported learning life skills by using cognitive processes of observational learning and reflections on experiences. Some athletes reported that life skills learning occurred automatically, which may suggest implicit cognitive learning.